Effects of the application of therapeutic massage in children with cancer: a systematic review - Juan Rodríguez-Mansilla; Blanca González-Sánchez; Silvia Torres-Piles; Jorge Guerrero Martín; María Jiménez-Palomares; Macarena Núñez Bellino
ABSTRACT Objective: to learn about the effects of the use of therapeutic massage in children with cancer. Method: systematic review of controlled clinical trials The search was conducted in November 2014 in the following databases: Pubmed, CSIC, Dialnet, Scopus, Cochrane and PEDro. Inclusion criteria were: clinical trials, published in English or Spanish, analyzing the effects of massage on the different stages and types of childhood cancer (between 1 and 18 years old). Results: of 1007 articles found, 7 met the inclusion criteria. Their authors use different massage techniques (Swedish massage, effleurage, petrissage, frictions, pressures), obtaining benefits in the symptoms present during the illness (decrease of pain, nausea, stress, anxiety and increase of white blood cells and neutrophils). Conclusion: therapeutic massage improves the symptoms of children with cancer, but there is a need for more research that may support the effects attributed to it.